Literature-in-English as a Tool for Fostering Intercultural Communicative Competence in Multicultural Classrooms in Nigeria - Oladotun Opeoluwa Olagbaju (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
Nigeria is a nation of several unique ethnic nationalities with diverse cultures. Cultural diversity has been identified as one of the factors responsible for growing civil unrest, insecurity and hate speeches in different parts of Nigeria. Multiculturalism is a common experience in several Nigerian states and the Nigerian education system. Efforts to inculcate intercultural competence among the members of the numerous ethnic groups and cultural identities in the country have been in form of legislation, convocation of national conferences and certain ‘political concessions’ to different ethnic groups. In spite of these efforts, very little has been achieved. The concern of this study is to discuss how education, through the tool of literature-in-English, can be engaged to teach intercultural communicative competence in multicultural classrooms. Recommendations were made on how to use literature-in-English to facilitate cross-cultural competence in Nigeria.